A tool to design fuzzy decision trees for sustainability assessment. (November 2017) - Bockstaller, Christian; Beauchet, Sandra; Manneville, Vincent; Amiaud, Bernard; Botreau, Raphaëlle
Abstract: Assessment of sustainability is a multicriteria problem that addresses several criteria belonging to various themes structured in sustainability dimensions. There is the need for a relevant aggregation method in addition to the disaggregated indicators. To face this challenge, we developed a new aggregation method, CONTRA, which is based on a decision tree using fuzzy sets. We attempted to combine the advantages of previous tools like DEXi and FisPro that ensure simplicity, flexibility and transparency while limiting subjectivity in the design of decision trees. The results of two examples of implementation in the agricultural sector and a sensitivity test highlight the functionalities of the tool and its discrimination potential. The possibility offered by the tool to correct predetermined decision rules makes it possible to cope with compensation between input variables, an important issue in aggregation. The next step will be the finalisation of the Excel prototype in a user-friendly software. Highlights: CONTRA is a new aggregation tool for multicriteria assessment of sustainability. CONTRA is based on decision trees using fuzzy sets. CONTRA combines the simplicity, flexibility and transparency of previous tools. CONTRA was designed to manage both weighting and compensation between criteria. CONTRA has already been successfully used in two research projects.